A pH‐Based Single‐Sensor Array for Discriminating Metal Ions in Water. Issue 10 (7th April 2022) - Bowyer, Amy A.; Mai, Anthony D.; Guo, Haobo; New, Elizabeth J.
Abstract: Human activities, such as mining and manufacturing, expose society and the natural environment to harmful levels of metal ions. Recently, optical sensor arrays for metal ion detection have become popular owing to their favourable features, such as facile sample preparation and the requirement of less expensive instrumentation compared to traditional, spectrometry‐based analysis techniques. Sensor arrays usually consist of numerous optical probes that are used in combination to generate unique analyte responses. In contrast, here we present an array that comprises a single fluorescent sensor, Coum4‐DPA, that produces unique responses to metal ions in different pH environments. With this simple sensing platform, we were able to classify 10 metal ions in different water sources and quantify Pb 2+ in tap water using just one fluorescent sensor, a few pH buffers and two sets of spectral data. This novel approach significantly decreases time and costs associated with probe synthesis and data collection, making it highly transferrable to real‐world metal sensing applications. Abstract : Fluorescent arrays for metal ions normally employ multiple fluorophores, whether as separate molecules or on macromolecular scaffolds. In an alternate approach, we use a single small molecule fluorescent sensor and only pH environment as a diversity source to accurately classify ten metal ions in different water sources.